Chromosome-Level Genome and Variation Map of Eri Silkworm Samia cynthia ricini - Kunpeng Lu; Jianghong Shen; Wengong Huang; Chengyu Zhan; Zhengqing Li; Shubo Liang; Kerui Lai; Qun Luo; Minjin Han; Xiaoling Tong; Fangyin Dai (Biology, 2025)
The eri silkworm Samia cynthia ricini (S. ricini) is an economically and scientifically significant lepidopteran species, though its genomic resources have remained limited. Here, we present a chromosome-level genome assembly for S. ricini generated through integrated long-read, short-read, and Hi-C sequencing data. The final 456.16 Mb assembly spans 14 chromosomes, exhibiting 98.5% BUSCO completeness and a 48.51% repetitive content. Functional annotation of the 15,729 protein-coding genes against five major databases (NR, SwissProt, Pfam, GO, and KEGG) revealed a maximum annotation rate of 92.71%, demonstrating high gene set quality. Comparative genomics with B. mori uncovered conserved syntenic blocks interspersed with chromosomal fusion/fission events and inversions. We further identified 4.27 million SNPs, 1.02 million InDels, and 53,367 SVs, establishing the first comprehensive variation map for this species. These genomic variations provide a foundation for marker-assisted breeding programs and trait association studies. All the genomic resources and interactive visualization tools were integrated into the SilkMeta database. This study establishes S. ricini as a pivotal resource for comparative lepidopteran genomics and accelerates molecular breeding programs for this agriculturally valuable insect.